The occurred error in microdosimetry calculations while using water instead of the body organs in proton therapy and a new formula for an estimate of the statistical uncertainty of microdosimetric quantities - Jahanfar, Somayeh; Anbaran, Hossein Tavakoli (Penerbit Universiti Kebangsaan Malaysia, 2022)
In many experimental and simulation researches, water phantom is used instead of most body organs. Therefore, in this study, we replaced the water phantom instead of some organs to calculate its effect on the proton stopping-power, and range and the consequence of deposited energy and microdosimetric spectra in small sites. Some organs such as the spleen, thyroid, pancreas, prostate, testis, and ovaries are considered. We calculated the proton stopping-power in these organs using the SRIM code. Then using these results, we wrote a program in the programming language of Fortran and computed the proton range and deposited energy in two sites of 1 and 100 micron. Also, using the Geant4-10-4 code, we simulated these sites and obtained microdosimetric spectra of protons at 1 and 5MeV energies. In order to compare different states, the frequency-mean lineal energy, dose-mean lineal energy, these statistical uncertainties and absorb dose in each case were calculated and reported. Also, we estimated the statistical uncertainty of quantities with a new formula. We observed that using water instead of the organs causes a significant error in the calculations of the range and the maximum relative difference percentage of 18% and 22% in deposited energy in 1 and 100 micron sites, respectively. These differences depend on the energy of the incident proton, organ, and size site. Also, this replacement changes microdosimetric spectra, the location, and intensity of the Bragg’s peak. The percent difference of location and intensity of the Bragg’s peak for water instead of the spleen is -8.66 and 13.42%, respectively. Therefore, using water instead of the body organs in microdosimetry calculations is not recommended.